Knowledge Management, Personality and Career Development Planning on Performance Through Innovative Behavior and Commitment of Bank Riau Kepri Employees - Puspita, Ola; Hendriani, Susi; ., Samsir; Efni, Yulia (Journal of Ecohumanism, 2024)
This research aims to analyze the influence of knowledge management, personality, and career development planning on the performance of managerial-level employees at Bank Riau Kepri through innovative Behavior and work commitment. This research is based on the results of employee performance assessments, which average in the excellent category each year. Meanwhile, the company expects employee performance to be in the outstanding category. Knowledge management, personality, and career development planning are predicted to influence the performance of managerial-level employees significantly. This research was conducted at Bank Riau Kepri Pekanbaru Riau Indonesia with a sample of 159 executive-level employees. The sampling technique used was stratified random sampling. The data collection technique used was a questionnaire/questionnaire and the data analysis technique used SEM Smart PLS. Based on the research results, knowledge management, innovative Behavior, personality, work commitment and career development planning are directly influenced by the performance of managerial-level employees at Bank Riau Kepri. Furthermore, it is known that innovative Behavior can mediate the influence of knowledge management on the performance of managerial-level employees and the impact of personality on the performance of managerial-level employees. Finally, it is known that work commitment can mediate the influence of nature on the performance of managerial-level employees and the impact of career development planning on the performance of managerial-level employees. These results prove that the variables of innovative Behavior and work commitment perform an intervening function in the pattern of influence of the independent variables (knowledge management, personality, and career development planning) on the dependent (employee performance).